Inflammatory bowel disease patients believe cannabis and cannabidiol oil relieve symptoms - Ayati Lala; Alexander Rodriguez-Palacios; Fabio Cominelli; Abigail Raffner Basson (Academia Medicine)
Background: Patients with Inflammatory bowel disease (IBD) often seek alternative therapies for symptom management. This study investigates the perceptions, consumption patterns, and reported outcomes of cannabis and cannabidiol (CBD) oil use among IBD patients and controls. Methods: A 37-question survey was administered to 139 participants (IBD patients, n = 93; control/non-IBD participants, n = 33) to assess usage frequency and beliefs regarding cannabis and CBD oil as treatment for IBD. The survey also evaluated the impact of these substances on IBD symptoms, quality of life, and opioid use. Results: Cannabis consumption was higher in IBD patients (57, 53.8%) than controls (15, 45.5%) with both groups strongly supporting medical cannabis use (IBD; 92, 86.8% vs. controls; 29, 84.9%). Most IBD patients believed cannabis (67, 63.2%), CBD oil (60, 56.6%), corticosteroids (77, 73.3%), and biologics/immunosuppressants (85, 81.0%) had a somewhat-extremely beneficial effect in relieving IBD symptoms. Over 50% of IBD cannabis users reported relief from abdominal pain, other pain, stress, anxiety, depression, and nausea/vomiting, with Crohn’s disease patients experiencing significantly more relief than ulcerative colitis patients for certain symptoms (p < 0.05). Notably, 19.4% of IBD patients reported decreased opioid use, and 14.5% reported induced remission with cannabis or CBD oil. Conclusions: Consumption of cannabis and CBD oil was perceived as beneficial for relieving IBD, with many reporting significant symptom relief from using these substances. The strong support of cannabis and CBD oil as medical treatments and therapeutic effects highlights the potential for cannabis and CBD oil as treatments in IBD.